Impacts of Digitization of Business Permits and Licenses in District 3 Quezon City - Alindajao, Ian Dave U.; Abbot, Neygen D.; Mariňas, Jayson B.; Malang, Bernandino P.; Vigonte, Florinda G. (Future Science / FSH-PH Publications, 2023)
This study aimed to determine the Impacts of Digitization of Business Permits and Licenses in District 3 Quezon City in terms of service satisfaction on time efficiency, reliability, cost-effectiveness, and convenience in business permit and license application of the business owners as the respondents of the study. The researchers used a descriptive method of research instruments to gather vital data from 380 business owners and guided the researchers in determining the result of the study. The researchers found that the respondents were very satisfied with digitizing business permits and licenses. It was recommended by the researchers that in order to enhance e-governance, the Business Permit and Licensing Department must include alert/reminder messages thru Short Message Service (SMS) in informing the status and deficiency of business permit and license application documents submitted by the business owners. Furthermore, there must be a system integration of all departments involved in processing business permits and licenses to ensure complete compliance in order not to hamper the business owners’ applications.